Jugamos a saltar para mejorar la coordinación motora - Flores Juárez, Anita (2019)
The purpose of the Professional Proficiency Work is to improve motor coordination in the psychomotor area in 4 year-old students of the initial level of the I.E.I No. 266 Jesus child of the Province of Julcan, La Libertad Región - 2019”_x000D_ Many have incorporated the game into their learning theories. The principal and always named Jean Piaget, in his theory of development, considers it part of the formation of the symbol. Like imitation, the game has a symbolic function, it allows the child to face an imaginary reality that, on the one hand, has something in common with the effective reality, but, on the other hand, moves away from it. Thus they practice mentally events or situations not present in reality. The game is dominated by assimilation, a mental process by which children adapt and transform external reality based on their own motivations and their internal world. We could say that the two main functions are: consolidate skills acquired through repetition and reinforce the feeling of being able to effectively change the world._x000D_ Muscular or motor coordination is the ability of skeletal muscles of the body to synchronize under parameters of trajectory and movement. Coordination is a complementary physical capacity that allows the student to perform orderly and directed movements to obtain a technical gesture._x000D_ In conclusion we affirm that the Work of Professional Proficiency is to improve motor coordination in the psychomotor area in students of school age of the initial level.